Virtuous mobility: moralising vs measuring geographical mobility in Africa - Pirie, Gordon H. (Afrika Focus, 2009)
Mobility practices, discourse and measurement need rethinking in an age of energy shortages, environmental anxiety and virtual mobility. Standard numerical indexes and other proxies for geographical mobility can be misleading, not least in formulating public policy. The extremes of spatial mobilities in Africa may require particularly sensitive consideration; the peculiar social, psychological and economic dimensions of geographical mobility on the continent certainly need registering. Yet the exceptionalism of the African case is overdrawn and the developmentalism in- herent in yearnings for more mobility is a short-term exaggeration. Revaluing totemic mechanised mobility is urgently required. The way we act on, and the way we think, talk and write about, geographical mobility needs reconceptualising in terms of fairness, equity, environmental justice, and human rights. Key words: Africa, development indicators, human rights, inequality, mobility, transport